Experimenting with emerging media platforms : Field testing the future - Pacheco, Dan.; Routledge Taylor & Francis Group (London : Routledge Taylor & Francis Group, 2023)
"Experimenting with Emerging Media Platforms teaches students in media tracks - journalism, advertising, film and public relations - how to independently field-test and evaluate emerging technologies that could impact how media is produced, consumed and monetized in the future. Taking a unique trial-and-error approach, the author encourages students to go against their desire for perfection and instead plunge into exercises with the full expectation that they will "fail" many times before they succeed. Through focused assignments, this book provides pointers on how to familiarise yourself with current technology including extended reality (XR, VR, AR, and MR), open-source coding, photogrammetry, aerial imagery using drones, automation, and artificial intelligence. Readers are invited to create and test their own hypotheses and work outside of their comfort zones to reach conclusions on how a technology could enhance storytelling for a particular audience. Through experimentation guided by workbook exercises, case studies from students and media practitioners, practical tips and reminders about ethical decision-making, students will learn how to work like explorers and civic hackers to enact change in the media landscape. Readers are invited to share their final field test results online through the book's companion website and social media channels, where the author will post links to further reading, coding templates for simple projects, and short video tutorials. Built around an established course being taught by the author and informed by over 20 years' experience in media industries, Experimenting with Emerging Media Platforms is essential reading for aspiring media professionals and students undertaking courses such as Emerging Media, Media Innovation and Media Startups. For additional resources, please see the companion website: https://www.emergingmediaplatforms.com/"--
Who can predict the future? -- Change theories -- Initiating your field test -- Open source technologies -- XR and The Metaverse -- AR -- Conducting your field test -- 360 photo and video -- Photogrammetry -- Data, AI, automation and bots -- Autonomous flying cameras -- Field testing the future -- Afterword: the edge of innovation.
Includes bibliographical references and index.
Keywords: Mass media -- Technological innovations; Digital media -- Technological innovations; Online social networks; Social media